A comparison of helical and spur external gear machines for fluid power applications: Design and optimization. (December 2019) - Ransegnola, Thomas; Zhao, Xinran; Vacca, Andrea
Highlights: A design parameterization of a helical/spur external gear machine was developed. An optimization procedure was developed for design of helical and spur gear pumps. Helical gears have more potential for better meshing stress ripple than spur. Helical gears also have more potential for compactness and efficiency. Spur gears offer more potential for flow ripple reduction than helical. Abstract: This paper addresses the problem of determining the relative performance of spur and helical external gear pumps (EGPs) for fluid power applications. Helical EGPs are commonly considered as quieter units than spur ones; however, there is no specific study reported in literature that proves such claim. Similarly, it is hard to find data indicating which design is better in terms of compactness or energy performance. To tackle this problem, a procedure is developed for virtual design optimization of both helical and spur gear EGPs. This includes addressing the two fundamental challenges of the work, parameterizing a generic EGP design and quantifying its performance. By applying this procedure, a genetic algorithm can continue improving from generation to generation, until the pareto optimal set of designs is identified for both helical and spur units. In the comparison of these, the differences between the two configurations will be identified and the fundamental question of this work can be answered; are helical gears 'better' than spur gears?